Efficacy and safety of imatinib mesylate (Gleevec®) and immunohistochemical expression of c-Kit and PDGFR-β in a Gynecologic Oncology Group Phase Il Trial in women with recurrent or persistent carcinosarcomas of the uterus - Huh, Warner K.; Sill, Michael W.; Darcy, Kathleen M.; Elias, Kevin M.; Hoffman, James S.; Boggess, John F.; Alvarez, Ronald D.; Long, Harry J.; O'Malley, David M.; Birrer, Michael J. (Gynecologic oncology, 2010)
This multi-institutional phase II trial assessed the activity and toxicity of imatinib mesylate and explored c-Kit and platelet-derived growth factor receptor (PDGFR)-β in recurrent or persistent uterine carcinosarcoma. Women with measurable uterine carcinosarcoma, who had a performance status of 0, 1, or 2 and had received up to two prior treatment regimens, were eligible and treated with a 600-mg daily oral dose of imatinib mesylate until disease progression or unacceptable toxicity. Endpoints included progression-free survival (PFS) ≥ 6 months, overall toxicity, PFS, overall survival (OS), and response. c-Kit and PDGFR-β were evaluated by immunohistochemistry in archival tumor. Twenty-six women were enrolled, 23 were eligible/evaluable, 1 was ineligible (wrong primary), and 2 were inevaluable (never treated). One subject had a PFS time ≥ 6 months, yielding the only patient with stable disease. All other patients had progressive disease ( n = 17) or were inevaluable for tumor response ( n = 5). Adverse events included grade 4 hypocalcemia ( n = 1) and grade 3 fatigue, dehydration and anorexia, genitourinary/renal, lymphatic, metabolic, and ocular toxicity ( n = 1 each, 4%). Positive expression of c-Kit or PDGFR-β was observed in 88% (14/16) or 40% (6/15) and in 56% (9/16) or 73% (11/15) of cases in the sarcoma and carcinoma component of the tumor, respectively. Expression of c-Kit in the carcinoma component appeared to be associated with worse OS. No other associations were notable. Imatinib mesylate was generally well tolerated but had minimal activity as a single agent in unscreened patients. The potential association between carcinomatous c-Kit and OS requires validation.